Implementation Article 5 Paragraph 1 of Regional Regulation Number 1 On 2018 Concerning Education Provision (Case Study of Homeless Children in Barabai Territory) - Siti Julaiha (Sharia Journal and Education Center Publishing, 2023)
ABSTRACT This paper is motivated by the existence of a regional regulation that regulates the government's efforts in organizing education, where every individual aged seven to fifteen years is required to carry out basic education as stipulated in regional regulation number 1 of 2018 concerning education implementation article 5 paragraph 1 which reads